Strategi Membangun E-Banking, Experiential Marketing dan Physical Evidence Terhadap Loyalitas melalui Kepuasan Nasabah Bank Syariah Di Surabaya - Liling Listyawati; Sri Utami Ady (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of e-banking, experiential marketing, and physical evidence on customer loyalty with satisfaction as a mediating variable in Sharia Banks in the city of Surabaya. The quantitative approach is used with the type of explanatory research. A total of 100 respondents were selected through the judgment sampling method. Data analysis was carried out using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method with the help of SmartPLS 4.0 software. The results of the study showed that physical evidence had a positive and significant effect on customer satisfaction, while e-banking and experiential marketing had a positive but not significant effect on satisfaction. Furthermore, customer satisfaction has a positive and significant influence on customer loyalty, which means that the higher the satisfaction, the more likely it is for customers to remain loyal. In addition, the results of the indirect influence test show that physical evidence has a significant effect on loyalty through customer satisfaction as a mediating variable. However, e-banking and experiential marketing did not show a significant mediation effect. Overall, this research model explains that the loyalty of Islamic bank customers in Surabaya is more determined by the satisfaction factor that arises from real experience and physical evidence of banking services.